The effect of photoperiod on the timing of spring migration in the Bewick's Swan - Rees, Eileen C (Wildfowl, 1982)
Bewick's Swans Cygnus columbianus bewickii floodlit from duck until 22.00 hr started their spring migration significantly earlier than birds illuminated until 20.00 hr; these latter, in turn, left before those receiving a natural photoperiod. The effects of variations in wind conditions and temperature and of snowfall, snowcover and disturbances, were also considered, but only the proportion of days with North to East ('head') winds had a significant influence on the departure pattern. In the case of food supplied to the birds the relevant factor was thought to be timing rather than the quantity of grain provided.